2021
DOI: 10.3390/cancers13164145
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cancer Cell Autophagic Responses by Graphene-Based Nanomaterials: Molecular Mechanisms and Therapeutic Implications

Abstract: Graphene-based nanomaterials (GNM) are plausible candidates for cancer therapeutics and drug delivery systems. Pure graphene and graphene oxide nanoparticles, as well as graphene quantum dots and graphene nanofibers, were all able to trigger autophagy in cancer cells through both transcriptional and post-transcriptional mechanisms involving oxidative/endoplasmic reticulum stress, AMP-activated protein kinase, mechanistic target of rapamycin, mitogen-activated protein kinase, and Toll-like receptor signaling. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 116 publications
(318 reference statements)
0
14
0
Order By: Relevance
“…rGO is widely used as a drug or gene delivery system and its use in breast cancer therapy has been suggested [20]. Several studies have shown cytotoxic effects of GO on normal, cancerous and bacterial cells, although toxicological information on rGO materials remains limited [11,13,21]. In our study, we examined the cytotoxic effects of rGO nanomaterials on breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…rGO is widely used as a drug or gene delivery system and its use in breast cancer therapy has been suggested [20]. Several studies have shown cytotoxic effects of GO on normal, cancerous and bacterial cells, although toxicological information on rGO materials remains limited [11,13,21]. In our study, we examined the cytotoxic effects of rGO nanomaterials on breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are no clear mechanisms by which rGO induces cytotoxicity. Various physiochemical properties of rGO, including size, shape, structure, hydrophobicity, surface functionalization, dose administration, purity and elemental composition, allow rGO to exhibit many mechanisms of action in cancer cells [9][10][11]. Key mechanisms that appear to be related to GFNs include the production of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene is isolated from crystalline graphite Graphene is a flat monolayer composed of a single atom thick, two-dimensional sheet of a hexagonally arranged honeycomb lattice [ 6 ]. Graphene-based nanomaterials (GNM) include nanodimensional flakes or ribbons of pure graphene, graphene oxide (GO) and reduced graphene oxide (rGO) all consisting of single graphene layers [ 7 , 8 ]. GNM have various applications and are generally used in the biomedical field in diagnostics, bio-imaging and drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…This process can lead to the breakage, modification, or further cross-linking of the molecular chains. Cellular proteins and DNA can, therefore, undergo modification or even a complete loss of their biological activities [ 144 ].…”
Section: Toxicitymentioning
confidence: 99%